2019
DOI: 10.1111/tbed.13188
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for multidrug‐resistant tuberculosis in northwest Ethiopia: A case–control study

Abstract: Ethiopia is one of 30-high burden multidrug-resistant tuberculosis (MDR-TB) countries globally. The aim of this study was to describe the characteristics of patients with MDR-TB and to investigate risk factors for MDR-TB relative to having drug-susceptible tuberculosis (TB), in northwest Ethiopia. A hospital-based, unmatched casecontrol study was conducted. Cases were all MDR-TB patients (i.e., resistant to at least rifampicin and isoniazid) who were confirmed by culture and drug-susceptibility testing whilst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Previous studies have also reported a relatively higher notification rate of TB in urban areas than in rural areas [11, 12]. There could be several reasons for this: the effect of urban residence on TB may be partially due to the higher HIV prevalence in urban areas [1316]; and higher transmission could also occur in urban areas as a result of overcrowding and higher population density [15, 17]. On the other hand, TB patients living in urban areas may have better access to TB diagnostic services and therefore more likely to report TB cases and be notified compared to patients living in rural areas where there is limited access to TB diagnostic services [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported a relatively higher notification rate of TB in urban areas than in rural areas [11, 12]. There could be several reasons for this: the effect of urban residence on TB may be partially due to the higher HIV prevalence in urban areas [1316]; and higher transmission could also occur in urban areas as a result of overcrowding and higher population density [15, 17]. On the other hand, TB patients living in urban areas may have better access to TB diagnostic services and therefore more likely to report TB cases and be notified compared to patients living in rural areas where there is limited access to TB diagnostic services [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…The synergy between TB and HIV infection is strong. While TB is the leading cause of death among people living with HIV [1], HIV infection is the most important risk factor for developing active TB [2, 3]. Tuberculosis and HIV co-infection has been a major public health challenge to the global efforts in achieving elimination goals for both diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Then, fulltext screening was conducted for 43 articles. Finally, after the full-text screening, 27 eligible articles were included in the study (Abay et al, 2020;Abdella et al, 2015;Adane et al, 2015;Alene et al, 2019;Arega et al, 2019;Assefa et al, 2017;Babure et al, 2019;Bedewi et al, 2017;Biru et al, 2020;Deressa et al, 2014;Desissa et al, 2018;Dessalegn et al, 2016;Fikre et al, 2019;Gobena et al, 2018;Hamusse et al, 2016;Hirpaet al, 2013;Jaleta et al, 2017;Mehari et al, 2019;Mekonnen et al, 2015;Mesfin etal., 2018;Mulisa et al, 2015;Mulu et al, 2015;Seyoum et al, 2014;Tadesse et al, 2015;Tesfay et al, 2016;Tsega et al, 2017;Welekidan et al, 2020). We presented the detail using the PRISMA flow diagram (Figure 1).…”
Section: Study Characteristicsmentioning
confidence: 99%